2020
DOI: 10.1002/ccd.29405
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta‐analysis of impact of baseline thrombocytopenia on cardiovascular outcomes and mortality in patients undergoing percutaneous coronary intervention

Abstract: Background Thrombocytopenia (TP) is associated with higher incidence of bleeding in the setting of percutaneous coronary intervention (PCI) leading to increased morbidity and mortality. Herein, we report a meta‐analysis evaluating the effects of baseline thrombocytopenia (bTP) on cardiovascular outcomes in patients undergoing PCI. Methods Literature search was performed using PubMed, Embase, Cochrane library and http://clinicaltrials.gov from inception till October 2019. Patients were divided into two groups: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 41 publications
(124 reference statements)
1
6
0
Order By: Relevance
“…Platelets initiate and augment the process of thrombi formation on a ruptured atherosclerotic plaque and mitigate early and late stages of atherosclerosis, predisposing patients to CV events 47. Despite the crucial importance of platelets in haemostasis, thrombosis and thromboinflammation, the prognostic value of elevated platelet counts is not considered in contemporary risk scores 3 10…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Platelets initiate and augment the process of thrombi formation on a ruptured atherosclerotic plaque and mitigate early and late stages of atherosclerosis, predisposing patients to CV events 47. Despite the crucial importance of platelets in haemostasis, thrombosis and thromboinflammation, the prognostic value of elevated platelet counts is not considered in contemporary risk scores 3 10…”
Section: Discussionmentioning
confidence: 99%
“…Baseline platelet count is increasingly recognised as an important determinant of both periprocedural and longer term PCI outcomes and has been investigated in a number of prognostic studies previously 4–9. Many of these previous reports have focused on thrombocytopenia that may occur postprocedurally or have characterised thrombocytopenia as a categorical variable without consideration of whether there is gradation of risk by absolute platelet count 5 10. Previous studies have suggested that thrombocytopenia is associated with both an increase in major bleeding and ischaemic events, with no consideration around whether this balance changes across different platelet counts.…”
Section: Introductionmentioning
confidence: 99%
“…Conceptually, patients with TCP are expected to fare worse post‐PCI compared to their counterparts with normal platelet counts. Indeed, this has been shown to be true in various studies examining outcomes of patients undergoing PCI who have sustained peri‐procedural TCP or even had chronic TCP 3 …”
mentioning
confidence: 84%
“…Prior PCI studies in TCP patients have consisted of single‐center observational studies, secondary analyses of randomized controlled trials, and analyses of large administrative databases 6–15 . Overall, these studies showed a trend toward increased hemorrhagic and ischemic complications after PCI in TCP 16 . In larger studies, platelet count was evaluated as a binary variable (present or absent) which does not allow determination of the risk associated with more severe degrees of TCP 12 …”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14][15] Overall, these studies showed a trend toward increased hemorrhagic and ischemic complications after PCI in TCP. 16 In larger studies, platelet count was evaluated as a binary variable (present or absent) which does not allow determination of the risk associated with more severe degrees of TCP. 12 The VA Clinical Assessment, Reporting, and Tracking (CART)…”
Section: Introductionmentioning
confidence: 99%